COMPETENT APPROACH TO THE PROCESS OF MODERN SOCIAL REQUIREMENTS FOR THE PROCESS OF PEDAGOGICAL EDUCATION - Rashidova Rano Ganiyevna (American Journals, 2023)
In this article, competence approaches to the process of modern social demands placed on the process of pedagogical education are presented. In addition, the concepts of "competence", "competence", "competent pedagogue" and "competent approach" were analyzed in the research on pedagogical education.
Keywords: pedagogical education process, modern social requirements, competence approach, competent pedagogue, etc.